Accumulation of CD103+ CD8+ T cells in a cutaneous melanoma micrometastasis. Issue 12 (25th December 2019) - Hochheiser, Katharina; Aw Yeang, Han Xian; Wagner, Teagan; Tutuka, Candani; Behren, Andreas; Waithman, Jason; Angel, Christopher; Neeson, Paul J; Gebhardt, Thomas; Gyorki, David E
Abstract: Objective: The immune system can halt cancer progression by suppressing outgrowth of clinically occult micrometastases in a state of cancer‐immune equilibrium. Cutaneous melanoma provides a unique opportunity to study the immune contexture of such lesions, as miniscule skin metastases are accessible to clinical inspection and diagnostic biopsy. Methods: Here, we analysed by multiplex immunofluorescence microscopy samples from a melanoma patient presenting with an overt and an occult in‐transit metastasis (ITM), the latter of which appeared as a small erythematous papule. Results: Microarchitecture and immune composition in the two lesions were vastly different. CD4 + and CD8 + T cells accumulated around the margin of the overt SOX10 + Melan A + ITM but were largely excluded from the tumor centre. By contrast, the occult micrometastasis contained only few SOX10 + Melan A − melanoma cells which were scattered within a dense infiltrate of T cells, including a prominent population of CD103 + CD8 + T cells resembling tissue‐resident memory T (TRM ) cells. Notably, almost every single melanoma cell in the micrometastasis was in close proximity to these TRM ‐like cells. Conclusion: Such results support the emerging concept that CD103 + CD8 + TRM cells are key mediators of cancer surveillance and imply an important function of these cells in controlling clinically occult micrometastases in humans. Abstract : Analysing an occult in‐transit metastasis in a melanoma patient, we identify CD103 + CD8 + T cells with a resident memory phenotype as the dominant T‐cell subset. Such results support the emerging concept that CD103 + CD8 + tissue‐resident memory T cells are key mediators of cancer surveillance and imply an important function of these cells in controlling clinically occult micrometastases in humans.